JURIDICAL ANALYSIS OF POLICE REGULATION NUMBER 6 OF 2023 CONCERNING POLICE RECORD CERTIFICATES (SKCK) AT THE DELI SERDANG CITY POLICE - Imam Hadi Mulia; Tri Reni Novita (CV. Barokah Publsiher, 2026)
This study aims to analyze the legal regulation concerning the addition of BPJS Health membership as a requirement in the issuance of a Police Clearance Certificate (SKCK), to review this policy from the perspective of state administrative law in terms of legality and the protection of citizens’ constitutional rights, and to examine the juridical and social implications of its implementation at the Deli Serdang City Police (Polresta Deli Serdang). The location for data collection in this study was Polresta Deli Serdang. Data were collected through document study. The data sources used in this research were secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The research method employed was normative legal research using a statutory approach and a conceptual approach. Data analysis in this legal research was conducted using qualitative analysis. The results of the study indicate that, formally, the addition of BPJS Health membership as a requirement has a legal basis; however, substantively, it raises issues related to the principles of proportionality, justice, and non-discrimination in public services. The implementation of this policy also affects public access to SKCK services, particularly for lower- and middle-income groups. Therefore, policy evaluation and regulatory harmonization are necessary to ensure that the provision of public services continues to guarantee legal certainty and the protection of citizens’ rights.